Lactoferrin in Bone Tissue Regeneration - Icriverzi, Madalina; Dinca, Valentina; Moisei, Magdalena; Evans, Robert W.; Trif, Mihaela; Roseanu, Anca (Current Medicinal Chemistry, 2020)
Among the multiple properties exhibited by lactoferrin (Lf), its involvement in bone regeneration processes is of great interest at the present time. A series of in vitro and in vivo studies have revealed the ability of Lf to promote survival, proliferation and differentiation of osteoblast cells and to inhibit bone resorption mediated by osteoclasts. Although the mechanism underlying the action of Lf in bone cells is still not fully elucidated, it has been shown that its mode of action leading to the survival of osteoblasts is complemented by its mitogenic effect. Activation of several signalling pathways and gene expression, in an LRPdependent or independent manner, has been identified. Unlike the effects on osteoblasts, the action on osteoclasts is different, with Lf leading to a total arrest of osteoclastogenesis. Due to the positive effect of Lf on osteoblasts, the potential use of Lf alone or in combination with different biologically active compounds in bone tissue regeneration and the treatment of bone diseases is of great interest. Since the bioavailability of Lf in vivo is poor, a nanotechnology- based strategy to improve the biological properties of Lf was developed. The investigated formulations include incorporation of Lf into collagen membranes, gelatin hydrogel, liposomes, loading onto nanofibers, porous microspheres, or coating onto silica/titan based implants. Lf has also been coupled with other biologically active compounds such as biomimetic hydroxyapatite, in order to improve the efficacy of biomaterials used in the regulation of bone homeostasis. This review aims to provide an up-to-date review of research on the involvement of Lf in bone growth and healing and on its use as a potential therapeutic factor in bone tissue regeneration.
Keywords: osteoclast